Chlorogenic Acid Isolation from Coffee as Affected by the Homogeneity of Cherry Maturity - Husniati Husniati; Devi Oktiani (Indonesian Coffee and Cocoa Research Institute, 2019)
Chlorogenic acid is a polyphenol compound which has an antioxidant properties. The objectives of this research are to understand and compare the characteristics of caffeine, chlorogenic acid, and polyphenolic content in Robusta coffee treated differently. These are necessary to find out effective postharvest methodfor chlorogenic acid extraction. There were two group of samples with the different treatment in process and post harvests. The coffee was treated differently during the sortation and classified into selected coffee of red cherry (fully mature cherry) and unselected coffee (partly mature cherry). The sortation was to maximize the chlorogenic acid content in green coffee bean sample from red cherry bean as the raw material. This research found that the contents of chlorogenic acid extract of green coffee bean from the selected red cherry was higher than the unselected. The HPLC analysis for chlorogenic acid contents of green coffeebean from the selected red cherry was 4.41%, it was higher than other samples tested.